Examining the potential causal relationships among smoking behaviors, blood DNA methylation profiles, and the development of coronary heart disease and myocardial infarction - Wenhua Li; Pan Dong; Yixiao Li; Jiaxin Tang; Siyang Liu; Ling Tu; Xizhen Xu (Clinical Epigenetics)
Abstract Background Smoking has been identified as a standalone risk factor for coronary heart disease (CHD) and myocardial infarction (MI), but the precise underlying mechanisms remain incompletely elucidated. Results In this study, we conducted a two-sample Mendelian randomization analysis to examine the impact of smoking behaviors (including smoking initiation, age of smoking initiation, cigarettes per day, and smoking cessation) and smoking-related DNA methylation at CpG sites on CHD and MI based on the UK Biobank dataset. Additionally, we included the FinnGen and Biobank Japan datasets as replications and performed a meta-analysis to combine the results from different data sources. We further validated our results using genetic colocalization analysis. In genomic analysis, we provided compelling evidence on the association between genetically predicted smoking initiation and increased susceptibility to CHD and MI. In epigenetic analysis, we identified 11 smoking-related CpG sites linked to CHD risk and 10 smoking-related CpG sites associated with the risk of MI based on the UK Biobank dataset. Subsequently, some of these CpG sites were further replicated using the FinnGen or BBJ datasets. Ultimately, a meta-analysis was conducted to integrate findings from various data sources (3 for CHD, and 2 for MI), revealing that 7 of 11 CpG sites were linked to CHD risk; whereas, 7 of 10 CpG sites were associated with MI risk. Furthermore, we performed genetic colocalization analysis and found that cg19744173 (FBLN7), cg00395063 (ARHGEF12), and cg16822035 (MCF2L) exhibited robust evidence of colocalization with coronary heart disease; whereas, cg19529732 (DIABLO), cg26405020 (FES), and cg08940075 (CNN3) demonstrated strong colocalization evidence with the risk of myocardial infarction. Conclusions Our research offers a novel insight into the impact of smoking on the susceptibility to CHD and MI through the lens of epigenetic DNA methylation.